Separate and combined effects of neurotoxic and lytic compounds of Alexandrium strains on Mytilus edulis feeding activity and hemocyte function. Issue 84 (January 2019) - Bianchi, Virginia Angélica; Langeloh, Hendrik; Tillmann, Urban; Krock, Bernd; Müller, Annegret; Bickmeyer, Ulf; Abele, Doris
Abstract: Multiple toxic and bioactive compounds produced by Alexandrium spp. cause adverse effects on bivalves, but these effects are frequently difficult to attribute to a single compound class. To disentangle the effect of neurotoxic vs lytic secondary metabolites, we exposed blue mussels to either a paralytic shellfish toxin (PST) producing Alexandrium spp. strain, or to an exclusively lytic compound (LC) producing strain, or a strain containing both compound classes, to evaluate the time dependent effects after 3 and 7 days of feeding. Tested parameters comprised signs of paralysis, feeding activity, and immune cell integrity (hemocyte numbers and viability; lysosomal membrane destabilization) and function (ROS production). Both compound classes caused paralysis and immune impairment. The only effect attributable exclusively to PST was increased phagocytic activity after 3 days and impaired feeding activity after 7 days, which curtailed toxin accumulation in digestive glands. Lysosomal membrane destabilization were more closely, but not exclusively, matched with LC exposure. Effects on circulating hemocyte integrity and immune related functions were mostly transient or remained stable within 7 days; except for increased lysosomal labialization and decreased extracellular ROS production when mussels were exposed to the toxin combination. M. edulis displays adaptive fitness traits to survive and maintain immune capacity upon prolonged exposure to environmentally relevant concentrations of PST and/or LC producing Alexandrium strains. Highlights: Mytilus edulis were fed with PST and/or LC Alexandrium producer strains for 3 and 7 days. PST transiently increased phagocytosis and produced a persistent impairment of feeding activity. PST and LC affected hemocyte integrity and decreased cell number and ROS production. Most toxic effects on hemocytes were either transient or remained stable within 7 days. Combined toxins increased deleterious effects on lysosomal stability and extracellular ROS production, after 7 days.